Frost and cold waves: an approach to news quality and framing in the journalistic coverage of cybermedia in Peru - Muguerza, Mario (2022)
This academic paper analyzes the informative treatment of the cybermedia on cold weather and frost inPeru. The main objective was to study the informative quality and the frames used by Agencia Peruana de Noticias Andina, El Comercio and La República in their digital articles. Through a mixed methodology, 139 articles published during 2021 were analyzed. The results show that most of the articles come from external media; official sources are prioritized; journalistic genres such as chronicle and reportage are left aside; multimediality is not enhanced; and the most used frames are meteorological and public affairs. The researchers concluded that the informative quality is deficient in terms of the informative agenda, the handling of sources and the diversification of genres. The problems are not exposed from the point of view of civil society and the participation of politicians is overemphasized.